A spatial decision support system (SDSS) for sustainable tourism planning in Johor Ramsar sites, Malaysia - Aminu, M. (2013)
The need for a sustainable approach in tourism development is very often addressed among the academia, the authorities and the stakeholders, as well as the apparent need for tools, which will guide the decision environment in evaluation and planning. This research aims to identify conservation and compatible areas for tourism development in Johor Ramsar sites, using spatial modeling in geographic information system (GIS). The study describes a methodological approach based on the integrated use of GIS and multi criteria decision evaluation (MCE) to identify nature conservation and development priorities among the wetland areas. A set of criteria was defined to evaluate wetland biodiversity conservation and development. Having defined the criteria, the next step was selecting suitable indicators and variables to measure the selected criteria. Subsequently the criteria were evaluated from conservation and tourism development point of view. These criteria were then weighted using the pair wise comparison technique of MCE and the results were integrated into GIS. Several conservation scenarios were generated so as to simulate different evaluation perspectives. The scenarios were then compared to highlight the most feasible and to propose a conservation and development strategy for the wetland areas. The generation and comparison of conservation and development scenarios highlighted the critical issues of the decision problem. This study represents an important contribution to effective decision-making because it allows one to gradually narrow down a problem. Â© 2013 Springer-Verlag Berlin Heidelberg.